ANALISIS PENGGUNAAN APLIKASI CANVA DALAM KOMPETENSI PROFESIONALISME PENDIDIK PADA PEMBELAJARAN KREATIF DAN INTERAKTIF DI KABUPATEN TANGERANG - Tantik Toharoh (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
This study examines the use of Canva in strengthening teachers’ professional competence, particularly in the planning and implementation of creative and interactive learning. The research is grounded in the demands of 21st-century education, which position digital technology mastery as an integral component of teacher professionalism. A qualitative descriptive approach was employed, with data collected through open-ended questionnaires involving 20 teachers from early childhood, primary, and secondary education levels in Tangerang Regency, Indonesia. The data were analyzed using thematic analysis, encompassing open coding, category development, and theme generation. Data validity was ensured through response consistency checks and repeated data review. The findings reveal three main themes: (1) the use of Canva as a means to enhance teachers’ efficiency and autonomy in designing learning media, (2) the strengthening of professional creativity through the use of diverse templates and visual features, and (3) Canva’s contribution to fostering more active learning interactions based on students’ learning responses. These results indicate that Canva functions not merely as a design support tool, but as a pedagogical medium that facilitates the development of teachers’ professional competence. This study contributes to the field of educational technology by providing empirical evidence of Canva’s role in reinforcing teacher professionalism across educational levels and by highlighting its relevance as an adaptive digital learning medium for creative and interactive instructional practices.